The villainess turns the hourglass. 1 - SANSOBEE (Comics author) (Ize Press, 2023)
"The vile Aria Roscent is sentenced to execution for her cruel and vicious misdeeds against her angelic half sister, Mielle. Even Aria herself believes it's what she deserves--until Mielle gleefully reveals that she was the true mastermind all along. The helpless Aria makes a final, fervent wish for a chance to redo everything just as the blade swings down...and snaps to attention at the dining room table as her fourteen-year-old self! Armed with knowledge of what's to come, Aria's ready to turn the tables on Mielle!"--